2009
DOI: 10.1111/j.1365-2702.2009.02953.x
|View full text |Cite
|
Sign up to set email alerts
|

The quality of home care nurses’ documentation in new electronic patient records

Abstract: The study contributes to identifying areas of improvement in documentation by nurses in home health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
13

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 29 publications
0
55
0
13
Order By: Relevance
“…Studies have shown that implementing an EHR does not unilaterally indicate that documentation comprehensiveness will increase [38,60]. Further studies should focus on nurses' actual knowledge in specific areas that CDSSs are designed to support, and these studies should evaluate the effects of CDSSs on nurses' knowledge in these specific areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that implementing an EHR does not unilaterally indicate that documentation comprehensiveness will increase [38,60]. Further studies should focus on nurses' actual knowledge in specific areas that CDSSs are designed to support, and these studies should evaluate the effects of CDSSs on nurses' knowledge in these specific areas.…”
Section: Discussionmentioning
confidence: 99%
“…The CIND has five ordered levels of increasing comprehensiveness (Table 3), and scores of 3, 4 and 5 meet the Norwegian recommendations [23]. The CIND has been used in several other studies, and tests of inter-rater reliability have produced Cohen's kappa values between 0.57 and 1.0 [25,[37][38][39][40][41].…”
Section: Data Collection and Outcome Measuresmentioning
confidence: 99%
“…Additionally, health care professionals in hospitals are obligated to advise and guide the municipal health care services about patients’ needs [20, 21]. Research has shown, however, that documentation of basic health care needs [22], as well as communication of these needs across health care settings, is generally poor [23–27]. …”
Section: Introductionmentioning
confidence: 99%
“…«Nedsatt evne til verbal kommunikasjon, relatert til afasi etter slag, fører til frustrasjon og nedstemthet» er et eksempel på en sykepleiediagnose med P(R)ES-struktur. Det er beskrevet at strukturerte og standardiserte maler bidrar til en mer fullstendig dokumentasjon (8,19,23,24). Det er også vist til at bruk av standardiserte terminologier forbedrer innhold i sykepleieplaner i tillegg til å øke antall intervensjoner og beskrivelser av tegn, symptomer og relaterte faktorer (7,14).…”
Section: Noe For Deg?unclassified